(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper presents new concepts of continuous multifunctions, called upper quasi θτ^(σ_1,σ_2)-continuous multifunctions and lower quasi θτ^(σ_1,σ_2)-continuous multifunctions. Moreover, several characterizations and some properties concerning upper quasi θτ^(σ_1,σ_2)-continuous multifunctions and lower quasi θτ^(σ_1,σ_2)-continuous multifunctions are considered.